Analysis of the Competitiveness and Export Performance of Indonesian Coconut Shell Charcoal Briquettes (HS 4402) in Saudi Arabia : RCA, EPD, and XModel (International Journal of Economics and Management Research, 2026)
Coconut shell charcoal briquettes are one of Indonesia’s leading export commodities with high demand in international markets, including Saudi Arabia. Although Indonesia remains the top exporter, export growth over the past decade has faced increasing competition from countries such as China, Malaysia, Vietnam, and Egypt. This study aims to analyze the competitiveness, export performance dynamics, and market potential of Indonesia’s coconut shell charcoal briquettes compared to its four main competitors in the Saudi Arabian market from 2014 to 2023. The methods employed include the Revealed Comparative Advantage (RCA) to measure comparative advantage, Export Product Dynamic (EPD) to assess export performance trends, and the XModel Potential Export Products to evaluate market potential. The RCA results indicate that Indonesia has a very strong comparative advantage (average RCA of 49.49), consistently surpassing its competitors. However, EPD analysis categorizes Indonesia as a “Lost opportunity,” meaning that while exports are growing, market share is declining, indicating untapped potential. The XModel analysis positionsIndonesia as a “Potential Market,” while Vietnam emerges as the only “Optimistic Market” with a strong RCA (13.97) and a Rising star EPD trend. These findings highlight Indonesia’s strong comparative advantage but emphasize the need for adaptive export strategies to convert potential into sustainable competitiveness.